SEASON OF MIGRATION TO THE NORTH: A DREAM OF RECONCILIATION BETWEEN TRADITION AND LIBERALISM - Al-Shraah, Sameer M. (European Scientific Journal, ESJ, 2015)
The main thesis of this paper suggests that al-Tayeb Salih’s Season of Migration to the North is best read as an attempt, though so difficult and complex, to make reconciliation between the Arabic, Islamic tradition and between the Western liberalism on the one hand, and between the colonized (Arab Sudanese) and the colonizer (the British Empire) on the other hand. It is a portraying of the failure that usually faced and still facing the Arab intellectuals who try to bring liberalism and modernism to the Arab World. As one of those Arab intellectuals, Al-Tayyib Salih tries, through Season of Migration to the North, to give us an image of how difficult the mission of those intellectuals is.